(untitled) (The International Journal of Educational Sciences and Arts, 2026)
The aim of this study was to investigate cognitive control and guided discovery among female students in the Early Years Education Department, and to identify the relationship between cognitive control and guided discovery among these students. The study adopted a descriptive-analytical approach, The researcher developed the two scales (cognitive control and guided discovery) and applied them to a sample of 150 female students in the Early Childhood Education Department. The results showed that early years education students possess cognitive control and also engage in guided discovery. Furthermore, the results revealed a strong positive correlation between cognitive control and guided discovery, which suggests that cognitive control is an effective educational approach that contributes to enhancing guided discovery among students, as it provides opportunities for experience-based learning and active interaction, leading to a deeper understanding and more effective and meaningful learning.